Context‐Dependent Effects of Ivermectin Residues on Dung Insects: Interactions With Environmental Stressors, Size, and Sex in a Sepsid Fly (Sepsis neocynipsea) - Jill Walker; Benjamin J. Mathews; Patrick T. Rohner (Ecology and Evolution)
ABSTRACT Coprophagous insects frequently encounter veterinary medication residues that are excreted unmetabolized in livestock dung. These residues often negatively affect insect survival, reproduction, and ecosystem services and may contribute to the rapid decline in insect populations. Ivermectin is an antiparasitic drug widely used to treat parasites in livestock. While it has long been recognized that ivermectin residues affect insect survival, the potential interactive effects between ivermectin exposure and other ecologically relevant abiotic stressors remain poorly understood. Here, we study these effects in the black scavenger fly Sepsis neocynipsea, which depends on cow dung for reproduction. Using a fully factorial experimental design, we test whether the effects of ivermectin exposure on adult survival interact with heat and desiccation stress and whether the severity of these effects depends on an individual's size and sex. We found that ivermectin exposure had strong negative impacts on adult survival overall, but that mortality was approximately three times higher in females compared to males. The combination of ivermectin exposure, heat, and desiccation stress drastically reduced survival. Interestingly, individuals simultaneously exposed to heat and ivermectin stress survived better—on average— than individuals only exposed to ivermectin, suggesting potential hormetic effects. Taken together, our findings highlight how the complex interactions between veterinary pharmaceuticals and abiotic stressors could drive changes in coprophagous insect populations and their ecological functions.